ANALISA KANDUNGAN Pb DAN Fe PADA AIR MINUM DALAM KEMASAN (AMDK) PRODUKSI PANTAI BARAT SELATAN ACEH - Zaulfikar Abbas; Muhamad Reza (Universitas Teuku Umar, 2017)
All minerals contained in drinking water, including Pb and Fe, shall be inaccordance with Regulation of the Minister of Health of the Republic of Indonesia No. 492/MENKES/PER/IV/2010, which shall not exceed 0.01 mg/l for Pb and 0.3 mg/l for Fe. The provision is also required against Bottled Drinking Water (AMDK). If the content is excessive can disrupt and endanger health.Based on Permenkes Number 492/2010, the researchers have conducted the test of Pb and Fe content of 7 (seven) brands of Bottled Drinking Water (AMDK) local production of the western-southern coastal area of Aceh province. In the study, researchers used descriptive methods based on laboratory test results. The sampling technique is done by purposive sampling, in which each brand is taken 3 (three) drinking water sample in glass packaging 220-230 ml from different market/location. The results of observation, researchers found 7 brands of Drinking Water In Packaging (AMDK). The test is repeated 2 times. So the total is 42 test samples. The results showed that from 42 test samples gave excellent results on Pb content, which of the seven brands of AMDK tested did not show the Pb content to the lowest limit that can be detected by Atomic Absorption Spectrosphotometry (SSA), which is 0.002 mg/l. The content of Pb is far below the requirement stipulated in Permenkes Number 492/2010, is not exceeding 0.01 mg/l. While the Fe content of the seven brands of AMDK tested gave varying values, but the content is still very low compared to the Fe content permitted Permenkes No. 492/2010, which does not exceed 0.3 mg/l. Where there are 2 brands of AMDK have Fe content ranging from 0.12 to 0.17 mg/l, while from 5 other brands of AMDK have Fe content ranges from 0.0113 to 0.0941 mg/l. So, from the results obtained it can be concluded that the seven brands of Bottled Drinking Water (AMDK) production area of South West Coast of Aceh is safe for consumption, because it does not cause the impact of Pb and Fe content is still far from the maximum set Permenkes No. 492/2010.Keywords: Pb, Fe, Bottled Drinking Water